Transects of urban CO2 measurements on a bicycle‐based atmospheric sensor. (5th July 2022) - Mazon, Jordi
Abstract : It is well known that CO2 is one of the main greenhouse gases. The traffic of non‐electric vehicles is the main contributor to the emissions of this gas in the cities, enhancing the urban heat island effect and increasing the dangers of global warming. The changes in the amount of CO2 across the city occur on a small urban scale, easily measured by a person moving around the city, whether it be walking or cycling. A handheld CO2 sensor capable of recording this gas, temperature, atmospheric pressure, and relative humidity was mounted on a bicycle to analyse local variations of this gas across a couple of cycling route transects in Barcelona city and a municipality within its metropolitan area. The results presented here show local CO2 variability, with some changes in concentration of up to 90ppm over distances of a few hundred metres (less than 1km). The influence of parks, urban forests, and gardens in absorbing the gas has also been identified. The measurements obtained with this technique demonstrate that using a bicycle as a scientific vehicle is a viable way to analyse the CO2 distribution in urban and suburban areas.